Cardiotoxicity associated with CTLA4 and PD1 blocking immunotherapy. Issue 1 (16th August 2016) - Heinzerling, Lucie; Ott, Patrick A.; Hodi, F. Stephen; Husain, Aliya N.; Tajmir-Riahi, Azadeh; Tawbi, Hussein; Pauschinger, Matthias; Gajewski, Thomas F.; Lipson, Evan J.; Luke, Jason J.
Abstract : Immune-checkpoint blocking antibodies have demonstrated objective antitumor responses in multiple tumor types including melanoma, non-small cell lung cancer (NSCLC), and renal cell cancer (RCC). In melanoma, an increase in overall survival has been demonstrated with anti-CTLA-4 and PD-1 inhibition. However, a plethora of immune-mediated adverse events has been reported with these agents. Immune-mediated cardiotoxicity induced by checkpoint inhibitors has been reported in single cases with variable presentation, including myocarditis and pericarditis. Among six clinical cancer centers with substantial experience in the administration of immune-checkpoint blocking antibodies, eight cases of immune-related cardiotoxicity after ipilimumab and/or nivolumab/pembrolizumab were identified. Diagnostic findings, treatment and follow-up are reported. A large variety of cardiotoxic events with manifestations such as heart failure, cardiomyopathy, heart block, myocardial fibrosis and myocarditis was documented. This is the largest case series to date describing cardiotoxicity of immune-checkpoint blocking antibodies. Awareness, monitoring of patients with pre-existing cardiac disorders and prompt evaluation by the treatment team is essential. Treatment including application of steroids is critical for patient safety.